Heroes wear masks : Elmo's super adventure - Jane, Lillian (Sourcebooks Wonderland, 2020)
"Today is a very exciting day--it's Elmo is heading off to school, and he wants to be a School Superhero! Join Elmo as he gets ready like a hero and learns about wearing masks and hand washing. It's going to be a SUPER day! With the help of Elmo and his mommy, this all new story from world-renowned education brand Sesame Workshop will help children combat school anxiety and understand new experiences like wearing masks, frequent hand washing, and social distancing. School Superhero reminds readers that it's super to help everyone stay healthy!" --